Phenotypic, molecular and pathogenic characterization of Colletotrichum scovillei infecting Capsicum species in Rio de Janeiro, Brazil - Renata Mussoi Giacomin; Claudete de Fátima Ruas; Viviane Yumi Baba; Sara Mataroli De Godoy; Claudia Pombo Sudré; Cintia dos Santos Bento; Maura Da Cunha; Ingrid Gaspar Da Costa Geronimo; Rosana Rodrigues; Leandro SA Gonçalves (PeerJ, 2021)
Anthracnose is a disease caused by Colletotrichum spp., one of the world’s most damaging sweet and chili pepper pathogens, especially in tropical and subtropical regions. In the state of Rio de Janeiro, anthracnose is one of the main obstacles for pepper crops. However, to date no research has focused on the identification and characterization of the pathogen, which is fundamental to understand the scope of the disease in the state. Thus, the correct identification of the fungal species and pathogenicity studies can provide important support for disease management and control, apart from identifying possible resistance sources for exploitation in peppers breeding programs. In this study, 11 Colletotrichum isolates were collected from peppers with typical symptoms in the Rio de Janeiro state. These isolates were characterized based on morpho-cultural characteristics and sequencing data from five regions (ITS, ACT, CAL, β-TUB and GAPDH), and the genetic variability was estimated by AFLP markers. Simultaneously, microscopy images of the colonization by the fungal species on unripe Capsicum annuum fruits were taken. Pathogenicity was tested and resistance sources were sought by means of infection of ripe and unripe fruits of 50 Capsicum baccatum accessions. The resulting data showed that all isolates belong to Colletotrichum scovillei specie. About the pathogenicity of Capsicum baccatum, differentiated, stage-specific responses, with higher resistance of ripe fruits were recorded. In addition, four possible sources of Colletotrichum scovillei resistance were detected among the tested accessions. The combination of these data can contribute to future studies on the interaction of Colletotrichum scovillei-Capsicum spp., a research line that is still unexploited in the main areas of this anthracnose fungus.